1971
DOI: 10.1007/bf01808863
|View full text |Cite
|
Sign up to set email alerts
|

Methyl methacrylate cranioplasty

Abstract: The use of methyl methacrylate for cranioplastic repair in 417 patients over a 13 year period has been presented. Its advantages have been noted as well as the indications and the operative technique. Infection has occurred in less than one percent, and half of these cases (2) were due to surgical errors.Operations for repair of cranial defects have been performed for many years, and a good historical account is given by Reeves 3. Many different materials have been used which have included bone (autogenous, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…Previous studies reported that a longer time interval between DC and CP increased the risk of SSI 12). Recently, however, Sundseth et al30) found no statistically significant relationship between the time interval from DC to CP and the risk for SSI.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reported that a longer time interval between DC and CP increased the risk of SSI 12). Recently, however, Sundseth et al30) found no statistically significant relationship between the time interval from DC to CP and the risk for SSI.…”
Section: Discussionmentioning
confidence: 95%
“…They have proven biocompatibility when they are in contact with vital tissues [6]. In present article heat polymerized acrylic stent was used instead of silicone T tube for replacement of stenosed tracheal segment.…”
Section: Discussionmentioning
confidence: 99%
“…Low morbidity and mortality are expected [1, 2, 3, 21, 23]. It is inexpensive, easily molded at the time of operation and associated with a short operative time.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate of methylmethacrylate cranioplasty specifically within the pediatric population has been quoted as high as 23% [6]. Further considerations in pediatric patients include durability of both the graft and the overlying skin which may be thin or atrophic [1, 3]. Autogenic bone is better suited for grafting into the immature skull, as it can provide protection and aesthetic function while also allowing for continued growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation